Assessment of root canal transportation of 2Shape and ProTaper gold in mandibular molar mesial canals: A micro–computed tomographic study. Issue 4 (23rd November 2020) - Nehme, Walid; Araji, Stephanie; Michetti, Jérôme; Zogheib, Carla; Naaman, Alfred; Khalil, Issam; Pages, Raphaël; Basarab, Adrian; Mallet, Jean Philippe; Diemer, Franck
Abstract: The aim of this study was to compare shaping abilities of Protaper Gold® (PTG) and 2Shape® (TS) by using a new automatic process and micro‐computed tomography (Micro‐CT). 32 first mandibular molars with two separate mesial canals were selected. Only mesial roots were prepared with PTG and TS. Pre‐ and post‐operative scans were performed using Micro‐CT to provide volumes with a voxel size of 20 μm. Volumes, non‐instrumented area, amount of transportation and centering ability in coronal, middle and apical third shaping time and procedural errors were recorded. TS and PTG increased the endodontic volume of 2.98 mm 3 (±1.56) and 3.21 mm 3 (±1.78) respectively with no statistical difference ( p = .168) and no procedural errors. No significant difference was found concerning canal transportation among groups but only within the same group PTG ( p value < .001) and TS ( p value < .001). The mean centering ratio was significantly different only between the section levels for PTG ( p value < .001) and TS ( p value = .01); it was significantly reduced in the cervical third. The percentage of untouched canal walls ranged between 29.78% (±15.145) and 36.60% (±11.968) respectively for PTG and TS with no statistical difference among groups ( p value = .168). TS and PTG with post machining heat treatment were able to produce centered preparations with no significant difference or procedural errors. TS system provided a shorter preparation time than PTG files. Abstract : Even with different design, taper, apical diameter and motion, the files 2Shape® and Protaper Gold® were able to produce centered preparations with no significant procedural errors. 2shape® system provided a faster preparation time, but none of the systems was able to touch the entire walls of the canal space which implies the necessity of supplementary measures to insure a thorough disinfection of the root canal system. Further investigations are needed to corroborate these results.